Family knowledge on newborn care - Ana Leticia Monteiro Gomes; Cristiane Rodrigues da Rocha; Danielle de Mendonça Henrique; Mirza Almeida Santos; Leila Rangel da Silva (Rev Rene)
Objective: analyzing the knowledge that families acquired on newborn care, before and after their participation in a motherfather- infant welcoming group. Methods: a quantitative and descriptive study that took place in a municipal health center, with 27 participants. Data were collected by a questionnaire applied before and after the educational activity, and was analyzed by comparing the answers of the items. Results: care actions properly modified were: the use of baby powder, soap, tea, objects in the navel, sun bathing time, correct hygiene of male genitalia, attention to child’s records and physiological eliminations. Conclusion: the families reported positive changes in newborn care through participation in health education activities, suggesting that the activity developed with caregivers can reduce risks to the health of newborn babies.